IMPLEMENTASI PEMBELAJARAN AKTIF KREATIF EFEKTIF DAN MENYENANGKAN (PAKEM) DAPAT MENINGKATKAN PRESTASI BELAJAR SISWA KELAS VIII A BIDANG STUDI SEJARAH KEBUDAYAAN ISLAM (SKI) DI MADRASAH TSANAWIYAH RAUDLATUL HUDA AL-ISLAMY - MUHAMMAD IRSYAD; MUHAMMAD FERI FERNADI; SUCI HARTATI; MUSTAFIDA (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
The main instruments for collecting data are: observation, interviews and documentation notes. Supporting factors and obstacles to the implementation of PAKEM in Islamic Cultural History (SKI) subjects, supporting factors include the school environment which is also a source of learning, motivation and leadership for teachers to conduct training, involve teachers in training activities in terms of learning methods and provide supervision to educators related to the learning process in the classroom, while the constraining factors include student motivation, teacher ability and the availability of learning facilities and media, the results of implementing PAKEM in SKI subjects at MTs Raudlatul Huda Al-Islamy are very good